Foreign and domestic takeovers in Germany: Cherry-picking and lemon-grabbing - John P. Weche-Gelübcke (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
This study focuses on ex ante performance of domestic and foreign takeover targets in Germany, one of the most important FDI inflow destinations worldwide. Using a new database from German official statistics, unconditional comparisons as well as binary response model estimations of takeover probabilities were performed for the manufacturing and service sector separately. The results showed a diametrically opposing impact of productivity and profitability on the takeover likelihood. This offers a conciliation of two supposedly opponent hypotheses, known as 'cherry-picking' and 'lemon-grabbing'. The results advocate assumptions of asset-exploiting and information asymmetries in favor of domestic investors but differ only marginally between foreign and domestic targets.
Keywords: F21; F23; G34; 330; Foreign ownership; Germany; acquisition; firm performance; services; inward FDI; multinational firms; productivity; Übernahme; Multinationales Unternehmen; Direktinvestition; Ausländisch; Unternehmenserfolg; Dienstleistungssektor; Produktivität; Deutschland